Mehman Mamedov: case management during and after coronavirus pandemic - article Editorial (Кардиоваскулярная терапия и профилактика)
On April 27, 2021, at the initiative of the Indonesian Heart Association, an online meeting was held with one of the leading cardiology experts in Russia, Professor Mamedov M. N.